Public education and misinformation on brain death in mainstream media. Issue 9 (25th July 2016) - Lewis, Ariane; Lord, Aaron S.; Czeisler, Barry M.; Caplan, Arthur
Abstract: Introduction: We sought to evaluate the caliber of education mainstream media provides the public about brain death. Methods: We reviewed articles published prior to July 31, 2015, on the most shared/heavily trafficked mainstream media websites of 2014 using the names of patients from two highly publicized brain death cases, "Jahi McMath" and "Marlise Muñoz." Results: We reviewed 208 unique articles. The subject was referred to as being "alive" or on "life support" in 72% (149) of the articles, 97% (144) of which also described the subject as being brain dead. A definition of brain death was provided in 4% (9) of the articles. Only 7% (14) of the articles noted that organ support should be discontinued after brain death declaration unless a family has agreed to organ donation. Reference was made to well‐known cases of patients in persistent vegetative states in 16% (34) of articles and 47% (16) of these implied both patients were in the same clinical state. Conclusions: Mainstream media provides poor education to the public on brain death. Because public understanding of brain death impacts organ and tissue donation, it is important for physicians, organ procurement organizations, and transplant coordinators to improve public education on this topic.